Simulation of the tribological properties of motor oils by the results of laboratory tests - Dykha, O.; Aulin, V.; Babak, O.; Диха, О. В.; Аулін, В. В.; Бабак, О. П. (TNTU and Scientific Publishing House “SciView”, 2019)
The purpose of this work was to create a calculation-experimental method for calculating the wear of lubricated friction units of machines based on a two-factor wear model (contact pressure – sliding velocity) with identification of their wear resistance parameters. To achieve this purpose it was necessary to obtain theoretical dependences for identification of wear resistance parameters in the wear models based on laboratory tests with various geometrical contact diagrams of lubricated samples. Analysis of known studies has shown that existing approaches required solution of complex systems of integral-differential equations or numerical methods that are unacceptable in the engineering practice. In this work a model of the wear of lubricated friction units of machines in conditions of boundary friction was obtained in a form of dependence of the wear rate on the dimensionless complexes of contact pressure and sliding velocity. The basis was the solution of the inverse wear of the contact problem for various geometrical schemes of contact. The contact diagrams corresponded to the actual forms of contact of the friction units of the machines: rolling bearings and sliding bearings, gears and others. The following equations were taken as the defining equations: the equilibrium equation in the contact, the continuity equation in the contact, and the approximating experimental dependence for the wear of materials. As a result of the solution, it has been obtained the simple algebraic formulas for calculating and identifying the parameters of the patterns of wear. It was realized that the installation has been developed for tests by means of program Solid Works and the numerical algorithm of the decision of a task on the basis of program MathCad. During the work it has been studied the influence of determining factors of sliding velocity and load on bearing wear. The obtained results were recommended for predicting wear of lubricated friction units of engines at the design stage and optimizing their design and operational parameters. Метою даної роботи було створити розрахунково-експериментальний метод розрахунку зносу мастильних вузлів тертя машин на основі двофакторної моделі зносу (контактний тиск - швидкість ковзання) з визначенням їх параметрів зносостійкості. Для досягнення цієї мети необхідно було отримати теоретичні залежності для ідентифікації параметрів зносостійкості в моделях зносу на основі лабораторних випробувань з різними геометричними контактними схемами змащених зразків. Аналіз відомих досліджень показав, що існуючі підходи потребують вирішення складних систем інтегрально-диференціальних рівнянь чи чисельних методів, неприйнятних в інженерній практиці. У цій роботі була отримана модель зносу мастильних вузлів тертя машин в умовах граничного тертя у формі залежності швидкості зносу від безрозмірних комплексів контактного тиску та швидкості ковзання. В основі лежало рішення зворотного зносу контактної задачі для різних геометричних схем контакту. Діаграми контактів відповідали фактичним формам контакту вузлів тертя машин: підшипників кочення та підшипників ковзання, шестерень та інших. В якості визначальних рівнянь були взяті такі рівняння: рівняння рівноваги в контакті, рівняння неперервності в контакті та приблизна експериментальна залежність від зносу матеріалів. В результаті рішення було отримано прості алгебраїчні формули для обчислення та визначення параметрів моделей зносу. Було зрозуміло, що установка розроблена для тестів за допомогою програми Solid Works і чисельного алгоритму рішення задачі на основі програми MathCad. Під час роботи було вивчено вплив визначальних факторів швидкості ковзання та навантаження на зношеність підшипника. Отримані результати були рекомендовані для прогнозування зносу мастильних блоків тертя двигунів на стадії проектування та оптимізації їх конструктивних та експлуатаційних параметрів.
Моделювання трибологічних властивостей моторних олив за результатами лабораторних випробувань
Keywords: wear; lubrication; laboratory testing scheme; problem of contact wear; contact pressure; engine; зношування; змащування; схема лабораторних випробувань; проблема контактного зносу; контактний тиск; двигун